Motorisation of Fishing in Andhra Pradesh: Studying the Scope and Impact of a Centrally Sponsored Scheme. - Raju, S. Surapa (2012)
The Government of India has introduced the Motorization of traditional crafts under Centrally Sponsored Scheme (CSS) with the main objective of technological upgradation of the traditional sector, to help fishermen reduce their physical strain and their area of fishing operations mainly to increase the fish catch, their income, and thereby to raise their socio-economic status. This field based study examines the impact of motorization scheme on fishing households of Andhra Pradesh. The paper is organized in three sections (i) system, procedures and constraints in motorization scheme; (ii) analysis of the motorization scheme and its impact on catch and incomes; and (iii) examined the socio-economic conditions of the beneficiary households. The results of the analysis show that most of the bankers have not shown interest in financing the fishing community due bad experience of previous repayment record. Huge difference in value of catch was observed particularly between the beneficiary and control group households. Most of the beneficiary households stated that motorization has improved their fish catch, incomes and socio-economic conditions.